RESPONSE OF THE GROWTH AND YIELD OF CIHERANG RICE (Oryza sativa L.) AND WEEDS ON THE DIFFERENT PLANTING METHODS AND WEEDING FREQUENCIES - Djoko Heru Pamungkas; Zamroni Zamroni; Suprih Sudradjat (Jurnal Agrivet, 2018)
This study aimed to observe the growth and yield of Chiherang rice (Oryza sativa L) and weeds in response of different planting methods and weeding frequencies. We conducted the study in Semampir, Argorejo, Sedayu Sub-district, Bantul District on April until August, 2018. We arranged field study using randomized complete block design in 3x2 factorials with 3 times repetition. First factor was Jajar legowo (J) stratified as 3 levels; 2:1 (J1), 4:1 (J2), dan 6:1 (J3). Second factor was weeding frequency in 2 levels which were 2 times in 14 and 70 hst (P1) and 3 times in 14, 49 and 70 hst (P2). Observed variables include Ciherang rice growth (plant height, total tillers, percentage of productive tillers, fresh and dried weight of each plant), components of rice yield (grain dry weight of each harvest, percentage of filled grains, yield of each hectares), and weeds (type of weeds, fresh and dry weight of weeds). We analyzed results using variance analysis with significant level of 5%, followed with 5% DMRT test. We found that application of jajar legowo planting method and weeding frequency do not correlates with all growth and weeding frequency variables of Ciherang rice and weeds. 2:1, 4:1 and 6:1 jajar legowo planting methods do not show significant impact both on Ciherang rice growth and yield, and also weeds. Both 2 times (14 and 70 hst) and 3 times (14, 49 and 70 hst) also do not have significant impact on all variables observed.Keywords: Jajar Legowo, Weeding Frequency, Ciherang Rice